Gyroscope and Accelerometer Sensor on the Lanange Jagad Dance Robot Balance System - Ahmad Sopi Samosir; Nuryono Satya Widodo (Buletin Ilmiah Sarjana Teknik Elektro, 2020)
In performing dance moves, humanoid robots are expected to move flexibly and not easily fall during dance moves. To reduce the risk of robots falling while performing dance moves, a balance control system using a gyroscope sensor and accelerometer from the MPU6050 is controlled through the Arduino MEGA 2560 PRO. Robots that have balance control, are able to maintain stability in track conditions that have a certain degree of slope. This balance control system uses the Kalman filter method for processing data from the gyroscope sensor and accelerometer in order to reduce the noise that occurs during the robot's balance process. From the results of the test, the percentage of the success rate of robots in rest was 88.8%, the percentage of success when the robot was running was 86.6%, and the percentage of success when the robot was walking with dancing was 75%. From the results of all tests, humanoid robot has a percentage of 83.4% after adding a balance control system and when the humanoid robot does not use balance control will only produce a percentage of success rate of 48.4%.